(untitled) (Journal of Pharmaceutical Negative Results, 2010)
Numerous researches are being done in the field ofpharmaceutical sciences worldwide in the academics andindustries. While industrial researches and their findingsare often converted to patents, most of the academicresearch works are attempted to be converted into researchmanuscripts and the researcher/group makes efforts topublish the findings in national or international journalsof repute. A published manuscript may be regarded as adocumented attestation of the research work and is peerreviewed before publication by experts relevant to the fieldof research. A published manuscript then becomes a readyreference source for extending the research work for takingit to another level by other research groups and also servesas a source of recognition of the researcher/group. Overall,the research findings documented in the form of researchmanuscripts give way for future generations to explore newand better or alternate findings, henceforth enduring thisnever-ending and ever-exciting process of research.